Comparison of parental satisfaction with strip crowns and primary anterior zirconia crowns in 3-5 years old children over 1 year - Mayank Sharma; Amit Khatri; Namita Kalra; Rishi Tyagi (Wolters Kluwer Medknow Publications, 2021)
Background: During the past decade, parental involvement for the selection of full coronal restorations for the primary anterior teeth of their children has been increased. Two most common anterior aesthetic full coronal restorations, the strip crowns and the preformed zirconia crowns, are available options. Aim: The aim of this study is to compare parental satisfaction with strip crowns and preformed primary anterior zirconia crowns over 1 year in 3-5 years old children. Materials and Methods: Forty maxillary primary incisors were restored by either strip crown or zirconia crown in 24 children. Permuted block randomization method was used for the allocation of participants. Twenty-four parents participated were recalled to fill the questionnaire over 1 year. One parent dropped out at the end of 1 year. Data were analyzed using the t-test and Chi-square test. P < 0.05 considered statistically significant. Results: Parents were satisfied with both types of restorations. Statistically significant relationship was found between overall satisfaction and durability (P = 0.004) with strip crowns and with the color (P = 0.043) in the zirconia crowns. The parents with the lower satisfaction levels with the durability of strip crowns and color of zirconia crowns rated high overall satisfaction. Conclusion: Parental overall satisfaction was higher for preformed primary anterior zirconia crowns than strip crowns. Almost equal number of parents was satisfied with all other parameters except for durability, which was more for zirconia crowns.